Entrepreneurial Innovation Mediating among Marketing Strategies and Venture Sustainability in Ethiopia's - Shashi Kant; Metasebia Adula; Fisseha Dejene Yadete; Kebede Asefa (Research Synergy Foundation, 2023)
This research aimed to examine, in the context of an African company, the effects of its marketing approach predictors on enterprise sustainability as measured by organisation performance. The researchers developed several strategies and statistics that were both descriptive and inferential. The sampling approach incorporated both probabilities and non-probability components and used a simple random sampling procedure. The data for this study was provided by Oromia International Bank, a representative organisation in Ethiopia, by investigating 426 of its customer base, including those working in modern organisations and sectors at the Bule-Hora branch. The investigation's final findings demonstrate that organisational sustainability is deteriorating and fewer marketing tactics are being implemented. The leading causes of these findings are a lack of worker dedication, a hostile work atmosphere, weak leader competency, and slow adoption of new technology. Related predictors were one of the main problems when entrepreneurial breakthrough mediation was implemented. A leader's ability is one of the most promising strategies for promoting organisational sustainability in Ethiopia. The researchers provided the appropriate body with recommendations on how to handle the predictions, resolve the problems encountered during the execution of marketing strategies, and eventually provide effective marketing strategy compliance and strong organisation sustainability.